O Rozpiętościach Belek Wspornikowych Ukształtowanych z Warunków Wyrównania Naprężeń - Ignaczak, J. (Engineering Transactions, 1959)
The problem under consideration is that of spans of cantilever beams designed with the condition of equalized edge stresses. Using elliptic integrals determining the variability of the cross-section along the axis of the beam, certain conclusions are drawn concerning the practical applicability of beams designed with such conditions.